WAYS OF MANIPULATIVE INFLUENCE ON PUBLIC SERVANTS - Zolotariov V.F.; Bilosorochka S.I. (Pressing Problems of Public Administration, 2017)
The article raises the issue of awareness by public servants of the need to reassess sociallynormalized rules of organizational behavior, based on manipulative interaction. Its applied aspectsare revealed and the possibilities of transition to open interaction are de ned as the improvement ofthe professional activity of of cials on the way to integration into the world and European space.